A new partitioned 1D LTNE continuum model for the simulation of 3D-shaped honeycomb absorbers. (1st April 2022) - Broeske, Robin Tim; Schwarzbözl, Peter; Hoffschmidt, Bernhard
Abstract: Porous absorber structures intended for open volumetric receivers of central tower power plants are receiving significant attention in current research. Due to the geometric complexity, volume-averaged continuum models are a common tool for the simulation of volumetric absorbers. Widely established for the investigation of ceramic foams, existing continuum models are less suitable for the simulation of honeycomb absorbers. 3D-shaped honeycomb absorber designs, i.e. absorbers with varying cross-sections, can pose additional challenges in the form of internal front-like surfaces, which are oriented perpendicular to the main channel axis. Due to the importance of the internal front-like surfaces w.r.t. absorption of solar radiation and convective heat transfer, a new partitioned 1D LTNE continuum model is proposed. The key innovation is the division of the absorber geometries into distinct sections forming a set of coupled LTNE models. The new 1D continuum model has been successfully validated against a 3D CFD model. For nine compared simulation cases, the calculated thermal absorber efficiencies differ on average 0.81 percentage points between the two models. Simulations have been conducted for the state-of-the-art HiTRec absorber and two new absorber geometries. The StepRec absorber, a monolithic channel design with characteristic step-pins created, via ceramic 3D screen printing out of SiSiC, reaches a thermal efficiency of up to 89.5 % for an air outlet temperature of 700 °C . A volumetric effect is predicted by for the new Emitec absorber, a channel geometry made of thin metal sheets, depending on the incident irradiation with efficiencies of up to 85.8 % at 700 °C . Highlights: A new LTNE model for the simulation of 3D-shaped volumetric absorbers was developed. The innovation of the model is the division of absorber geometries into distinct sections. The 1D model has been successfully validated against a reference 3D model.